Social Embodiments: Prenatal Risk in Postsocialist Germany - Erikson, Susan L. (Anthropologica, 2022)
Anthropologists have linked bodies to social histories, events, and structures by way of a presence of illness or physical pathology. The social embodiment of risk evident in a hospital in former East Germany at the millennium was conceptually different: women described bodies marked by absences—of pregnancy, employment and feelings of safety. Central to the theoretical concerns of social embodiment in this article are observations of how the pregnant body embodies competing notions of risk. This article shows how notions of prenatal risk can illustrate the ways in which social embodiment can be not only a presence, but can also manifest as reproductive absence, hesitation and ambivalence.